Release of prostaglandins during contraction of the human umbilical vein on reduction of temperature. - Boura, A L (1979)
Flow rate was measured through the vein of the human isolated umbilical cord perfused at constant pressure (40 mmHg) at 37.5 degrees C and 20 degrees C. At the latter temperature the flow was decreased by 50.9% when compared with a mean of 201 ml/min at 37.5 degrees C indicating venospasm. Indomethacin (10 microgram/g) effected a highly significant reduction in the venous spasm caused by lowering the temperature. After indomethacin pretreatment, changing the cord temperature from 37.5 degrees C to 20 degrees C caused a mean decrease in flow of only 3.1%. When the effluent from the vein was passed over rat isolated stomach fundus and colonic strips, cooling of the cord was accompanied by contractions of the isolated tissues characteristic of prostaglandins. These results suggest that prostaglandins are involved in temperature-induced closure of the human umbilical vein after birth.